Vehicle load identification control system and functional module architecture - SI HONGLU; LIU ZENGYUE; DENG TAO; LI YIHUA; YIN LIANZUO; HOU SHENGDONG; ZENG KAILIAN; LIU SHUANQI; ZHU GAOHUA (2018)
The invention discloses a vehicle load identification control system and a functional module architecture. The vehicle load identification control system and the functional module architecture comprise a signal acquisition and processing module, an output shaft speed slope calculation module, a transmission output torque calculation module, a load factor calculation module, a load factor normalization processing module, a load factor filtering module, a target position calculation module and other functional modules. The vehicle load identification function combines dynamics of the vehicle, environmental conditions and road conditions, uses the knowledge of the automobile dynamics, and uses the fuzzy control theory to identify the load of the vehicle and adjust the shift reference speed onthe ramp according to three input signals of the pedal throttle size of a driver, the transmission output torque and the speed, and the optimal position of the vehicle on the ramp is calculated. 本发明公开了种车辆的负载识别控制系统及功能模块构架，其包括